Cardiac Involvement in Human Immunodeficiency Virus Infected Patients: An Observational Cardiac Magnetic Resonance Study - Yan, Chengxi; Li, Ruili; Guo, Xiaojuan; Yu, Huan; Li, Wenhuan; Li, Wenqiao; Ren, Meiji; Yang, Minglei; Li, Hongjun (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To investigate the subclinical imaging changes in terms of myocardial inflammation and fibrosis and to explore the risk factors associated with myocardial fibrosis by cardiac magnetic resonance (CMR) approach in a Chinese HIV/AIDS cohort. Methods: We evaluated myocardial function (cine), myocardial inflammation (T1, T2), and myocardial fibrosis (through extracellular volume fraction [ECV] and late gadolinium enhancement [LGE]) by a multiparametric CMR scan protocol in a total of 68 participants, including 47 HIV-infected individuals, who were divided into two groups: asymptomatic HIV (HIV+) (n = 30), and acquired immunodeficiency syndrome (AIDS) (n = 17), and 21 healthy controls. Results: HIV-infected patients had lower left (55.3 ± 6.5 vs. 63.0 ± 7.9%, P < 0.001) and right ventricular systolic function (35.9 ± 15.7 vs. 50.8 ± 9.3%, P < 0.001). Radial systolic strain (30.7 ± 9.3 vs. 39.3 ± 9.4%, P = 0.001), circumferential systolic strain (−17.5 ± 2.6 vs. −19.4 ± 2.7%, P = 0.008), and longitudinal systolic strain (−9.4 ± 5.7 vs. −12.8 ± 3.1%, P = 0.012) were also decreased in HIV. Native T1 relaxation time (1,337.2 ± 70.2 vs. 1,249.5 ± 47.0 ms, P < 0.001), ECV value (33.5 ± 6.2 vs. 28.5 ± 2.9 ms, P = 0.026), and T2 relaxation time (45.2 ± 3.5 vs. 42.0 ± 2.6 ms, P = 0.001) were higher in HIV-infected patients compared with controls. Myocardial fibrosis, predominantly in the mid-inferior wall, was detected in 24.4% of the HIV-infected patients. HIV+ had a significantly lower value of ECV [29.1 (26.1, 31.8) vs. 35.2 (31.8, 41.9) %, P < 0.001] and frequency of LGE [3/25 (8%) vs. 7/16 (43.8%), P = 0.014)] compared with AIDS. AIDS was associated with myocardial fibrosis. Conclusions: HIV-infected patients were associated with changes in myocardial function and higher rates of subclinical myocardial inflammation and fibrosis, which were more abnormal with greater severity of the disease. AIDS was associated with myocardial fibrosis, where the observations supported earlier initiation of antiretroviral therapy in the Chinese HIV/AIDS cohort.